Disability-Related Disparities in Access to Health Care Before (2008–2010) and After (2015–2017) the Affordable Care Act - Kaye, H. Stephen (Am J Public Health, 2019)
Objectives. To explore the effect of the Affordable Care Act (ACA) on disparities in access to health care based on disability status, as well as age, income, race, and ethnicity. Methods. In this study, I used logistic regression to analyze nationally representative data from 128 000 respondents to the US National Health Interview Survey from 2008 to 2010 and 2015 to 2017. Outcome variables were uninsurance over the previous 12 months, delayed or forgone health care for reasons of cost, and having a regular provider at a doctor’s office or health clinic. Results. Over the period when the ACA was implemented, large existing disparities in access to health care were reduced for people with certain types of disabilities, young adults aged 19 to 25 years, and low-income families. Conclusions. The ACA improved overall access to health care and reduced some disparities, but substantial disparities persist. Disability status remains associated with much greater risk of delayed or forgone care, and mental health disability is associated with greater likelihood of uninsurance. Public Health Implications. The ACA partially achieved its goals and must not be weakened or rolled back. Further policy efforts are needed to address the remaining disparities.